Mudanças no uso da terra em um hotspot de biodiversidade neotropical e seus efeitos sobre as abelhas Euglossini - Gomes, Brunna Machado Leão (2022)
Agricultural expansion threatens multiple species, including native bees, especially on Cerrado, where the major natural savannas and forests were replaced by agricultural exploration. Here we studied the effects of land-use changes on euglossine bees’ diversity and morphology. We evaluated bees’ communities in pasture, soybean crops, and eucalyptus plantations, and we investigated if availability differences between the land use cause differences in corporeal size and asymmetry. During six sampling months, using aromatic baits and traps we collected 1399 orchid bees’ males belonging to 11 species. We observed higher species richness and abundance in natural areas. Eulaema nigrita males represented 91,4% of all specimens, being the only species that occurred in all land uses, besides, presenting corporeal size differences between the land uses. Our results indicate that savannas and forest conversion lead to Euglossini bees’ fauna homogenization, causing a poor subset community. The lower abundance of El. nigrita on eucalyptus plantations indicates that some land uses can be an adverse event for a generalist species as this conversion causes environmental quality loss for Euglossini. Males from eucalyptus, pasture, or soybeans plantations were smaller than those from savannas and natural forests, as on eucalyptus the FA level was higher than it was on natural forests. We emphasized legislation importance to Cerrado preservation, as to guarantee also native bee preservation.